The Role of Educational Programs in the Treatment of Bronchial Asthma in Schoolchildren of the Chechen Republic - Aset Kh. Ibisheva; Madina R. Shakhgireeva; Saihat A. Shamsadova; Linda S. Uspanova; Asya B. Khildikharoeva; Linda V.-M. Dzhabrailova; Kamilla E. Efendieva (Педиатрическая фармакология, 2024)
Background. The main component of the treatment of bronchial asthma is to achieve complete control over the disease. The aim of the study is to examine the role of educational programs in the treatment of bronchial asthma in schoolchildren of the Chechen Republic.Methods. The educational programs included group and individual classes, which were conducted at the allergy school of the specialized Department of Allergology and Immunology of the E.P. Glinka Republican Children’s Clinical Hospital by an allergologist-immunologist. Educational meetings were held once a week for 2 months, their duration was 1–1.5 hours. Initially and every 3 months for one-year, bronchial asthma control was assessed based on the results of the Asthma Control Test (ACT), the number of emergency room visits, hospitalizations, attacks of shortness of breath stopped at home, missed days at school, the use of systemic glucocorticoids, indicators of pulmonary function test (PFT), the level of nitric oxide in exhaled air. The subjects were divided into two groups: group A —trained, group B — did not participate in educational programs. The subjects were represented by two age subgroups: group IA — 7–8 years old (n = 24), group IIA — 13–14 years old (n = 13). The control group consisted of 37 children who did not undergo allergy school training, who were observed on an outpatient basis by an allergist-immunologist: group IB — 7–8 years old (n = 23), group IIB — 13–14 years old (n = 14).Results. 3 months after the educational activities, the lack of control over bronchial asthma, according to the results of the ACT, was noted only in 10.8% (4) of patients, whereas in the comparison group — in 59.5% (22). The PFT study recorded an increase in the volume of forced exhalation in 1 second in children who attended allergy school (p < 0.05). A comparative analysis of the frequency of emergency room visits and hospitalizations revealed a decrease in the studied indicators in groups IA and IIA (p < 0.05). The number of missed days at school due to bronchial asthma was significantly lower in children after educational activities — 16.1% (6) and amounted to less than 14 days. Attacks of shortness of breath for 12 months occurred only in 18.9% (7) of patients and were stopped independently, their frequency ranged from 1 to 3, and the use of systemic glucocorticoids in arresting an attack was not recorded among children who attended allergy school.Conclusion. Thus, our study confirmed the high importance of educational programs in the treatment of bronchial asthma, which are an additional tool for achieving disease control and allow timely prevention of disease progression.